2022
DOI: 10.1302/0301-620x.104b6.bjj-2022-0080.r1
|View full text |Cite
|
Sign up to set email alerts
|

Developing a minimum common dataset for hip fracture audit to help countries set up national audits that can support international comparisons

Abstract: Aims The aim of this study was to explore current use of the Global Fragility Fracture Network (FFN) Minimum Common Dataset (MCD) within established national hip fracture registries, and to propose a revised MCD to enable international benchmarking for hip fracture care. Methods We compared all ten established national hip fracture registries: England, Wales, and Northern Ireland; Scotland; Australia and New Zealand; Republic of Ireland; Germany; the Netherlands; Sweden; Norway; Denmark; and Spain. We tabulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…This study has described and appraised a broad body of literature regarding research and audit in the Republic of Ireland published since 2005. It has revealed recent practices in long-term outcome collection and recording after acute Outcomes collected as part of recent hip fracture research in Ireland are broadly in line with those suggested by the international Fragility Fracture Network minimum common dataset for hip fracture audit, namely mortality, re-operation, mobility, residence, and bone protection medication [7]. There were varying time points of outcome collection in studies included in the current review.…”
Section: Discussionmentioning
confidence: 65%
“…This study has described and appraised a broad body of literature regarding research and audit in the Republic of Ireland published since 2005. It has revealed recent practices in long-term outcome collection and recording after acute Outcomes collected as part of recent hip fracture research in Ireland are broadly in line with those suggested by the international Fragility Fracture Network minimum common dataset for hip fracture audit, namely mortality, re-operation, mobility, residence, and bone protection medication [7]. There were varying time points of outcome collection in studies included in the current review.…”
Section: Discussionmentioning
confidence: 65%
“…Similar such studies are unlikely to be feasible now. Future work should utilise existing clinical audit mechanisms to monitor long‐term effects on a population‐wide level, and the compilation of data from multiple national hip fracture audit programmes (adhering to a minimum common clinical dataset) would ensure generalisability to a range of regions and healthcare contexts (Hall, Duckworth, et al., 2021 ; Johansen et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid data-sharing between regions in the form of low-cost and agile audit collaborations should be developed, with wider adoption of the revised 2022 Fragility Fracture Network Minimum Common Data Set for Hip Fracture Audit, and a pragmatic approach to information governance processes in order to facilitate cooperation. 22 These measures will ensure that future emergency audit responses can be commenced with reduced lead times, greater diversity and generalizability to global populations, and larger sample sizes through compilation of datasets using a meta-audit approach. 23 …”
Section: Lessons For Future Epidemics and Pandemicsmentioning
confidence: 99%